2020
DOI: 10.17763/1943-5045-90.2.295
|View full text |Cite
|
Sign up to set email alerts
|

“I Hesitate but I Do Have Hope”: Youth Speculative Civic Literacies for Troubled Times

Abstract: In this essay, Nicole Mirra and Antero Garcia explore how young people from six demographically distinct communities across the United States understand the social and political issues affecting their lives, engage in storytelling and dialogue across differences, and collaboratively imagine humanizing and hopeful civic futures. Drawing from critical race perspectives on democracy and civic education, and with an expansive vision of the nature and purpose of literacy, Mirra and Garcia develop a specula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 23 publications
0
52
0
1
Order By: Relevance
“…And, in a symbiotic relationship, youth are translating these visions into civic action in digital and non-digital settings. It is in light of the current moment of heightened U.S. scrutiny on political discourse and partisanship that we seek to understand how the radical possibilities of shape-shifting can better inform speculative civic literacies that “utilize difference as a source of civic generativity and creativity, and embody commitments to mutual humanization as sources of hope for a more equitable democratic future” (Mirra & Garcia, 2020, p. 297).…”
mentioning
confidence: 99%
“…And, in a symbiotic relationship, youth are translating these visions into civic action in digital and non-digital settings. It is in light of the current moment of heightened U.S. scrutiny on political discourse and partisanship that we seek to understand how the radical possibilities of shape-shifting can better inform speculative civic literacies that “utilize difference as a source of civic generativity and creativity, and embody commitments to mutual humanization as sources of hope for a more equitable democratic future” (Mirra & Garcia, 2020, p. 297).…”
mentioning
confidence: 99%
“…These silences, in the context of social discourse that serves to normalize policing (Seigel, 2017) may further harden dominant ideologies of law enforcement within and beyond school campuses. In public schools-spaces ripe for learning about democratic deliberation and practicing citizenship (Kahne & Westheimer, 2003;Mirra & Garcia, 2020)controversial discussions can prepare students to advocate for their communities. Given the salience of police and policing to the well-being of communities, the absence of these conversations in K-12 schooling suggests that students will be inadequately prepared to question dominant ideologies and to engage democratically around urgent questions of communal import.…”
Section: Discussionmentioning
confidence: 99%
“…In scholarship on schools, researchers have also articulated how educators might work toward abolition of the institution of policing and the carceral state both within their campuses and beyond them, and how many have fallen short in doing so (Meiners, 2011;Shange, 2019;Turner & Beneke, 2020). The existence of these radical conversations on policing in schools suggests the possibility for students to engage in "speculative civic literacy" in their classrooms (Mirra & Garcia, 2020), "restorying" dominant narratives of policing and imagining new political realities for public safety. While abolitionist conversations are at the forefront of activist and intellectual discourse about the police and schools, we shall address here how opportunities to challenge the institution of policing appear, if at all, in what students are expected to learn in their classrooms.…”
Section: Law Enforcement As a Core Component Of Structural Oppressionmentioning
confidence: 99%
“…Connected to pedagogy, speculative composing practices and, more specifically, restorying, present pedagogical frameworks for enacting critical literacy practices in the teaching of composition. While my own study was not conducted in a classroom, Mirra and Garcia (2020) have demonstrated the potential of using restorying in ELA (English language arts) classrooms to develop young peoples' speculative civic literacies through composing and dialogue. As they explain, speculative civic literacies challenge "normative stories," while honoring young peoples' "experiences, relationships, and dreams for the future" (p. 297).…”
Section: In Conclusion: a Happy Beginningmentioning
confidence: 99%